Knowledge and Utilization of Family Planning Methods among people living with HIV in Kathmandu Valley - Bhoosal, Anshu; Parajuli, Riya; Karki, Namrata (Health Prospect, 2022)
Background: HIV is a major global health issue, targeting the immune system and making the body prone to diseases. People living with HIV mostly face societal stigma and fear of disclosure resulting in discrimination of accessing health facilities leading to multiple sex partners, increased sexual activity and less use of condoms. HIV positive women are at risk of transmitting HIV to their infants and their partners. Thus, the family planning services if provided to PLHIV can help to improve their and families health. In addition to, it reduces the risk of mother-to-child transmission (PMTCT). Family planning is seemed to be a cost effective strategy for preventing mother to child transmission of HIV (PMTCT). In Nepal, people living with HIV/AIDS were found to experience stigma and discrimination, ultimately resulting in discrimination of accessing health facilities. The purpose of this study is to explore the knowledge of family planning methods and identify factors affecting the current utilization of such methods among HIV infected men and women attending ART sites of Kathmandu Valley. The study is expected to contribute in enhancing the present understanding of PLHIV towards family planning. Methods: The cross sectional descriptive method was used for the research. The study followed Population proportion to size method for the calculation of the respondents from four ART sites of Kathmandu Valley. Structured questionnaire used previously in similar research has been adopted with necessary question related to dual contraceptive use. Results: The mean age group of the respondents was (39.16 ± 6.969) years. More than two third respondents (69.5%) were Hindu. 34.8% respondents were married at the less than 20 years of age. Almost three- fourth of the PLHIV (74.4%) were literate where more than three fourth (79.3%) their spouses were literate and educated. About half of the respondents (43.9%) were found to be involved in professional/ technical/ managerial. More than half of the respondent’s spouses (63.4%) were HIV positive. All the respondents (100%) respondents had disclosed their status to their partners. Neither the respondents nor their partner had desire of further child. 28% of neither respondents nor their partners had used the family planning methods before HIV diagnosis. More than half (60.4%) of the respondents had sexual intercourse prior to last 6 months. 15.9% of the respondents positively responded to use of dual protection. Only 11% either respondents or their partners had used the emergency contraceptive pill. 17.7% respondents did not use any family planning. This study revealed that almost half of the respondents (48.8%) had the good knowledge on the use of contraception. Conclusion: The use of dual protection is much less than the half of the respondents. Therefore, counseling and health education towards motivating PLHIV on using dual FP methods to avoid the risk of HIV, STIs and unplanned pregnancy is encouraged.